Characteristics of Coronary Artery Disease Patients Who Have a Polymorphism in the Cholesterol Ester Transfer Protein (CETP) Gene - (:unkn) unknown (INT INST ANTICANCER RESEARCH, 2019)
Background/Aim: Cholesterol ester transfer protein (CETP) is responsible for the transformation of high density lipoprotein (HDL) to low density lipoprotein (LDL) and is a risk factor for atherosclerosis. Our study investigated the association of the rs5883 CETP gene polymorphism with HDL and LDL levels, in 45 coronary artery disease patients and 45 control patients. Materials and Methods: CETP gene polymorphism was detected using Real Time-Polymerase Chain Reaction (RT-PCR). Lipoprotein levels were measured using Quantimetrix system. Results: There were lack of associaition regarding CETP polymorphism in atherosclerosis and HDL and LDL levels (p>0.05) BMI was higher among coronary artery disease patients (CADP) compared to the control group (28.97 +/- 6.38, 26.52 +/- 4.39 respectively, p<0.03). Frequency of CADP (82.6 %, n=19) who were taking treatment was higher (17.4 %, n=4) (p<0.00). The frequencies of hypertension and type-2 diabetes were higher among CADP (p<0.00). Families of CADP have more CADP (p<0.02). Small HDL particle levels were higher in the control group (p<0.00). Conclusion: In Turkey, BMI, and frequencies of hypertension and type-2 diabetes were higher among CADP than among healthy controls. Furthermore, the genotypes of the rs5883 CETP gene polymorphism did not differ between CADP and healthy controls.
Keywords: Cholesterol ester transfer protein; polymorphism; atherosclerosis; coronary artery disease; real-time PCR; DENSITY-LIPOPROTEIN CHOLESTEROL; RISK; ASSOCIATION